Auracle - Rosati, Gina (New York : Roaring Brook Press, 2012)
A teenaged girl who has the power to astrally project finds her body taken over by a dead classmate, and must find a way to reclaim it if she wants to save herself and her friend who is accused of murder
Keywords: Astral projection -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Occult fiction; Love stories; Fiction; Juvenile works